UNILATERAL STENTING OF RENAL ARTERY STENOSIS IN A PATIENT UNDERGOING HEMODIALYSIS TREATMENT IMPROVES RENAL FUNCTION AND DECREASES BLOOD PRESSURE – EIGHT YEARS LONG-TERM RESULTS. (June 2018) - Neumann, C.L.; Schulz, E.G.
Abstract : Objective: The therapeutic procedure for the treatment of atherosclerotic renal artery stenosis is subject to controversy. Current guidelines however stipulate a consistent screening for indications of secondary hypertension. Design and method: Case history: Female patient, 81 years old, blood pressure measured in practice: 130/70 mmHg, impaired general condition, lower leg edema, over the course of 6 months increasing uremia. 1998 Initial diagnosis of coronary heart disease, 1999 Initial diagnosis of hypertensive nephrosclerosis. Regular- and color-coded duplex-sonography of the kidneys: Left: Cirrhosis of the kindney, no flow signal. Right: 9.4 cm × 4.5 cm × 5.0 cm. Due to uremia initiation of hemodialysis treatment via implanted Demers-Catheter. Intervention/angiography: Filiform, severely calcified ostial stenosis of right renal artery, functional subtotal occlusion. Profound ostial stenosis and cirrhosis of left kidney. Blood pressure 190/105 mmHg. Multiple percutaneous transluminal catheter angioplasty/ cutting balloon intervention. Subsequent bare metal stent implantation (Liberte 5.0 mm × 16 mm), followed by immediate high-pressure post-dilatation. Post interventional abrupt drop in blood pressure to high-normal values. Results: After three weeks hemodialysis treatments, therapy could be discontinued. After two years blood tests still provide stable laboratory values in the asymptomatic patient. Patient was free of symptoms. The required antihypertensives intake was significantly reduced (4-fold, mid-dose after one year and 3-fold mid-dose after two years) while maintaining optimal blood-pressure values. Color-coded duplex-sonography confirmed excellent perfusion of right kidney consistently over the course of one year and even eight years after dilatation. Even after eight years serum-creatine is 1.2 mg/dl. Figure. No caption available. Conclusions: Our case confirms importance of a patient-centered, individual decision for or against interventional treatment of atherosclerotic renal artery stenosis. Here, both reduction of blood pressure and preservation of renal function have to be considered. On left handside cirrhosis of the kidney was diagnosed (< 8 cm) with a complete absence of perfusion signal. On contrary, parameters of right kidney (> 9 cm, Parenchyma-RI < 0.8) allowed hemodynamic as well as functional success of an intervention to be expected. After eight years there are good results after intervention. Blood pressure is well controlled under reduced medication, dialysis is still not become necessary.